LiveScore: Real-Time Notation in the Music of Harris Wulfson. - Barrett, G. Douglas; Winter, Michael (Contemporary Music Review, 2010)
LiveScore is the title given to an interactive music piece and a software tool created by composer, multi-instrumentalist, improviser, and software programmer Harris Wulfson (1974-2008). The software allows network streaming of real-time notation delivered to one of several client computers. The interactive music piece consists of this real-time notation system set up for audience control. The authors describe both the musical work and the software and touch briefly upon the unique musical background of this visionary composer.